The applicability of the doctrine of constitutional avoidance to constitutional adjudication in Zimbabwe - Zvekare, Tawanda Rest (Midlands State University, 2019)
This study looks at the doctrine of constitutional avoidance as well as the doctrines of subsidiarity and ripeness and their application in constitutional litigation in Zimbabwe especially as they relate to the fundamental rights and freedoms set out in Chapter 4 of the Constitution. The purpose of this research is to assess whether their application is in accordance with the duty placed on all institutions at every level to respect, fulfil, promote and protect the rights and freedoms in Chapter 4 in terms of section 44 of the Constitution of Zimbabwe. The study looks at justiciability and mootness in passing. The study assesses this duty in the context of courts of constitutional jurisdiction in applying the doctrines of constitutional avoidance, subsidiarity and ripeness. The study goes through a series of case law from Zimbabwe and concludes that the application of the doctrines in Zimbabwe is not consistent with the duty placed on the judiciary in terms of section 44 of the Constitution. It then looks at the approaches taken by the United States of America and South Africa in the application of the same doctrines. Recommendations are made from the approaches of these countries aimed at coming up with an application of the doctrines which is consistent with the constitutional duty placed on the judiciary at every level.